Instilling Character Values Through Teacher Strategies - Abidin Muhammad; Sajjad Ali (Institut Studi Islam Muhammadiyah Pacitan, 2025)
The application of character education has now begun to be proclaimed by various educational institutions ranging from elementary to secondary levels, therefore it is necessary to study the success of implementing the implementation of character education. Teachers have a special position in the step of cultivating these character values, the aim is to create the next generation with noble character. Learning carried out by a teacher is dealing with a number of students who all want to be noticed. Students will develop optimally through positive teacher attention, otherwise negative attention will hinder the development of students. The purpose of this study was to determine the teacher’s strategy to instill the values of character education in students at MIN 1 Metro and MIS Al Khoiriyah. This study used a qualitative approach with the type of case study research and a multisite research design. The results of this study indicate that the teacher’s strategic approach is by analyzing SK, KD, and material indicators. Implementation of teacher strategies with action and implementation of worship. Evaluation of teacher strategies contains inhibiting factors: a) Facilities and infrastructure, b) Students, c) technological development, while supporting factors: a) Cooperation of all related parties, b) Optimizing coaching.